Maturidî ekolün İslam iktisadi ve siyasi düşüncesine etkileri - Ergün, Nihat (My University, 2017)
İnsanın kendisini, rolünü, hayatı ve kainatı doğru okuma, anlama ve anlamlandırma çabasında Hanefi-Maturidi anlayışa göre aklına en büyük yardımcı olarak gönderilen kitap ve peygamberin doğru anlaşılmasında ana İslami akım olan Sünni, Hanefi-Maturidi anlayışın siyasi ve iktisadi düşüncemize etki ve katkılarını araştırdık. Bu çerçevede insanların bir arada yaşmalarının sonucu olan siyasi ve idari eylem, kural ve kurumların, ihtiyaçların karşılanması gereğinin sonucu olan iktisadi eylem, kural ve kurumların doğal yapısını öncelikle Kur’an ve Sünnetteki doğal haliyle ele aldık. Kur’an’ı ve Peygamber’i inisiyatif alarak ve içtihat yeteneğini kullanarak anlayan ve uygulayanların, aynı zamanda Hanefi-Maturdi anlayışın da sahabe içindeki öncüsü sayılan Hz. Ömer’in özellikle siyasi ve ekonomik hayata dair anlayış ve uygulamaları inceledik. Adeta bir usta çırak ilişkisi içerisinde Hz. Ömer’in Talebesi Abdullah b. Mes’ud’dan kendi talebelerine onlardan da Ebu Hanife ve talebelerine bu anlayışın nasıl intikal ettiğini, hukukun, siyasi ve ekonomik hayatın ve bu alandaki ahlak ve erdemin inşasında nasıl bir metodoloji, görüş ve duruş geliştirdiklerini, gerektiğinde bedel ödeyerek günümüze kadar örnek olacak bir anlayışı nasıl canlı tutup taşıdıklarını tespit etmeye çalıştık. Onların bozulan itikadi zemini düzelterek yeniden kurdukları hukuki, siyasi ve ekonomik anlayışı eserleriyle ve örnekleriyle ele aldık. Hilafet merkezi Bağdat ve yakın çevresindeki bozulma ve kargaşa Ebu Hanife ve öğrencilerinin geliştirdiği anlayışın Semerkand havzası ve Maveraünnehir bölgesinde İmam Maturdi ve talebeleri ile yeni bir hüviyet kazanmasını, bozulan akıl-vahiy dengesinin yeniden kurulmasını, karmaşık hale gele gelen bilgi kaynaklarının kargaşadan arındırılmasını, böylece akıl-vahiy dengesi içinde doğru bilgiye dayalı yeni bir anlayışın kurulup geliştirilmesini zaruri hale getirdi. Bu çerçevede özellikle İmam Maturidi’nin hem bir kelam alimi, hem bir hukukçu, hem de dirayetli bir müfessir olarak iktisadi ve siyasi anlayışımıza doğrudan veya dolaylı bir şekilde etki eden görüşlerini analiz ettik. Esas amacının tefekkür ve istidlalin önünü açmak olduğunu ve doğruyu bulmanın ve anlamanın ancak bu şekilde mümkün olacağını vurgulayan İmam Maturidi’nin çizgisinden ilerleyerek çağdaş bazı sorunlar üzerinde tefekkür ve istidlalde bulunan ilim adamı, aydın ve mütefekkirlerin görüşlerine, arayışlarına da yer vererek günümüzde yaşanan siyasi çalkantı, mezhep çatışmaları, özgürlük, geri kalmışlık, faiz, kredi, vergilendirme konuları hakkındaki yaklaşımları değerlendirdik. Bütün bunları yaparken Ebu Hanife ve Maturidi’in mevaliden sayılması veya Türk olması nedeniyle Arap karşıtı veya Türk tipi Müslümanlık gibi faztezi sayılabilecek yaklaşımlara sıcak bakmadık. Zira bu iki büyük insanın açtığı çığır, geliştirdiği düşünce, görüş ve duruşun millileştirilmesinden çok evrenselleştirilmesi gerektiği sonucuna vardık.

İn order to undersatand the book and the prophet which are, especially in Hanefi-Maturidi view, sent as the greatest assistant to human mind in the sense of the reading, understanding and interpreting himself, his role, the life and the universe;We searched for the effects and contributions of Sunni, Hanefi-Maturidi conception, the main strand of Islam on the political and economic thought. In this framework, the natural structures of political and administrative actions, rules and institutions, which are the results of people’s living together, also, economic actions, rules and institutions, which are the result of the necessity of meeting people’s needs are discussed primarily as they are stated in the Qur'an and the Sunnah. We have studied the understanding and practices of those who understand and live the Qur'an and the Prophet by taking initiative and using his / her ijtihat (ruling case) ability, and also the understanding and practices of Hz. Omar, who is thought as the leader of Hanefi-Maturdi conception among companions of the Prophet, especially about political and economic life We tried to find out how this conception is transferred from Abdullah b., Mes'ud who is student of Hz.Omer to his students and from them to Abu Hanife and his students as in the context of a master apprentice relationship, what kind of a methodology, viewpoint and posture they developed in building law, political and economic life and moral and virtue in this area, how they kept alive and carried on an understanding which is seen as a model today. We studied the legal, political and economic understanding that they have reconstructed by correcting the distorted faith grounds with their works and examples. Distortion and turmoil in the caliphate center Baghdad and its immediate vicinity made it necessary for the conception developed by Abu Hanifa and his students, to acquire a new identity with Imam Maturdi and his students in the Samarkand basin and the Maveranin region, to re-establish the distorted mind-revelation balance, to remove the confusion from information sources that became complicated, and thus, to establish and develop a new understanding based on correct knowledge in reason-revelation balance. In this framework, we have analyzed the views of Imam Maturidi, both as a kalam scholor, as a jurist, and as a decisive glossator, influencing our economic and political understanding directly or indirectly. We examined the approaches about political turbulence, sectarian conflicts, freedom, backwardness, interest, credit, and taxation issues that have taken place in today's world by including in the opinions and searches of scholars, intellectuals and thinkers who have contemplated and made inferences about some contemporary problems by proceeding on the line of Imam Maturidi, who emphasizes that his main purpose is to open the way of thought and inference, and that it is only possible to find and understand the truth in this way. While conducting this study, we have not lean towards to the approaches that can be considered as fantasy such as anti-Arab or Turkish-type Islam, because of the fact that Abu Hanife and Maturidi are Turkish or counted as mevali (non Arabic Muslims). Then, we conclude that the ideas, perspectives and stances, that these two great people have developed and broken new ground, need to be universalized rather than nationalized.
Keywords: Ekonomi; Görüş ve düşünceleri; İktisat; İslam dini; Maturidi; Maturidî; Maturidi Economy; Tarih